PHARMACOTHERAPY OF ATTENTION-DEFICIT/HYPERACTIVITY DISORDER IN ADULTS: A SYSTEMATIC REVIEW WITH META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS (2015-2025) - Costa, Bernardo Tolentino; Rodovalho, Ana Laura Almeida; Nishino, Fabio Kendy; De Oliveira, Bruno Santos; da Silva, Rafael; da Fonseca, Cauã Cabral Magno; de Araujo, Paulo Ricardo Rocha; de Lima, Lis Melo; Fantin, Luiz Gustavo Barbosa; dos Santos, Amanda Souza; Marques, André Mateus; Cardoso, Erick Silva; et al. (Seven Editora, 2026)
Background: Attention-deficit/hyperactivity disorder (ADHD) affects approximately 2.5% of the adult population globally. Multiple pharmacological agents are available, yet comparative efficacy and safety data remain limited.Objective: To systematically review and meta-analyze the efficacy, safety, and tolerability of pharmacological treatments for adults with ADHD using randomized controlled trials (RCTs) published between 2015 and 2025. Methods: Systematic searches were conducted in PubMed/MEDLINE, Embase, and Cochrane Library for double-blind, placebo-controlled RCTs in adults (≥18 years) with ADHD diagnosed according to DSM-IV, DSM-5, or ICD-10/11 criteria. Primary outcome was symptom reduction measured by validated scales (ADHD-RS, Conners, SNAP-IV). Secondary outcomes included adverse events, discontinuation rates, and functional improvement. Risk of bias was assessed using Cochrane RoB 2.0. Meta-analysis employed random-effects models with standardized mean differences (SMD) and 95% confidence intervals (CI). Heterogeneity was evaluated using I² statistics. GRADE methodology was applied to assess evidence quality. Results: Thirty-seven RCTs (n=2,289 adults) were included. Methylphenidate extended-release demonstrated the largest effect size (SMD: −0.92; 95% CI: −1.08 to −0.76), followed by lisdexamfetamine (SMD: −0.96; 95% CI: −1.17 to −0.76), mixed amphetamine salts (SMD: −0.81; 95% CI: −0.95 to −0.67), and atomoxetine (SMD: −0.48; 95% CI: −0.64 to −0.33). Guanfacine showed moderate efficacy (SMD: −0.66; 95% CI: −0.94 to −0.38). Stimulants demonstrated superior acceptability compared to non-stimulants. Adverse events were generally mild and dose-dependent. Heterogeneity was moderate (I²: 30–50%). Conclusion: Stimulant medications, particularly methylphenidate and lisdexamfetamine, represent first-line pharmacological treatments for adults with ADHD, with large effect sizes and favorable tolerability profiles. Non-stimulants offer alternatives for patients with contraindications or comorbidities. Evidence quality ranges from moderate to high for stimulants and low to moderate for non-stimulants.